Analysis And Instabilaty Of A Control System - Bhattacharjee, Swarup (International Journal of Scientific Research and Management (IJSRM), 2015)
Control systems in an interdisciplinary field covering many areas of engineering and sciences. Control systems exist in many systems of engineering, sciences, and in human body. Some type of control systems affects most aspects of our day-to-day activities. The study and design of a control system includes various steps such as modeling, simulation, analysis and optimization. Physical laws namely Kirchhoff’s laws, Newton’s laws, laws of thermodynamics. The Control System Toolbox has large number of built in functions which can be used for analysis and design of control systems.